Implementasi ISAK 35 pada Pelaporan Keuangan Masjid Al-Ihsan Jorong Taratak Nagari Kubang - Yohana Desfitri; Nini Sumarni (Lembaga Yasin AlSys, 2026)
Although mosque financial reporting as a nonprofit entity has received attention in various studies, studies that specifically discuss the implementation of Interpretation of Financial Accounting Standards (ISAK) 35 in mosque financial reporting remain limited. This study aims to determine the implementation of ISAK 35 and to analyze the financial statements of Al-Ihsan Mosque, Jorong Taratak, Nagari Kubang, based on this standard. This study employed a qualitative approach with a case study design, involving informants consisting of the mosque chairperson and treasurer selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed inductively through the stages of data reduction, data display, and conclusion drawing. The results showed that the mosque’s financial reporting was still carried out simply in the form of recording cash receipts and cash disbursements, and had not yet been prepared in accordance with the ISAK 35 components, which include a statement of financial position, statement of comprehensive income, statement of changes in net assets, statement of cash flows, and notes to the financial statements. These findings contribute to the development of accountability and stewardship theory in nonprofit organizations while broadening understanding of mosque financial reporting practices. This study concludes that the implementation of ISAK 35 is important for improving the transparency and accountability of mosque financial management, so mosque administrators and related parties need to enhance their understanding through training and assistance. The implications of this study include theoretical contributions to the development of public sector and Sharia accounting, as well as practical contributions for mosque managers, while also opening opportunities for further research on the implementation of accounting standards in other nonprofit entities.